Smokeless tobacco consumption in South Asia: a review of the health programmes and interventions to reduce consumption - Neha Mehta; Surabhi Sharma (Universitas Aisyiyah Yogyakarta, 2022)
Over 290 million smokeless tobacco (SLT) users are located in South Asia (SA), accounting for 80% of the global burden of disease. Consequences of consumption include oral cancer, ischemic heart disease and still births, leading to an increased morbidity and mortality. The lack of a global mandate has led to less regulation and greater affordability of smokeless tobacco products, causing smokers to switch to these products. The need to identify effective interventions to reduce smokeless tobacco consumption is evident. This review will appraise the effectiveness of health programmes and interventions used to reduce SLT consumption in SA and identify areas for future research. Literature was found by searching Global Health, Medline, Web of Science, Google Scholar and Pubmed, using key terms. Literature was then systematically assessed using inclusion and exclusion criteria to yield 19 pieces of literature for this review. Four broad intervention categories were identified and appraised using different criteria for effectiveness. Each intervention had varying levels of effectiveness which depended on external factors. The lack of literature evaluating SLT interventions was noted and feasibility was estimated where necessary. Although interventions had a high effectiveness in some areas, many demonstrated low effectiveness due to their complex multi-sectoral nature. Further research is required to identify effective strategies and barriers precluding implementation.